Meanings assigned by families about children's chronic disease diagnosis - Daiani Modernel Xavier; Giovana Calcagno Gomes; Marta Regina Cezar-Vaz
ABSTRACT Objectives: to understand the meanings assigned by family caregivers about children's chronic disease diagnosis. Methods: qualitative study, which used as theoretical framework the Symbolic Interactionism, and methodological, the Grounded Theory. It was held in a pediatric unit in Southern Brazil, in 2016, through interviews submitted to open and axial analysis, with the participation of 20 family caregivers of hospitalized children. Results: relatives, interacting with the nursing/health staff, perceive children's disease at birth. They are diagnosed with chronic disease by the physician and deny it. Subsequently, they accept and seek information on care. Conclusions: the results pointed out the stages that relatives experience by assigning meanings to about children's chronic disease diagnosis. These meanings provide subsidies for nurses' actions, which need to be aware of children's and family's needs in order to offer comprehensive and humanized care.